Does Reconstruction with Reimplantation of Sterilized Tumor Bone Provide Survival Benefit in Diaphyseal Osteosarcoma?. (20th January 2020) - Nayak, Prakash; Gulia, Ashish; Puri, Ajay
Abstract : Does reimplantation of sterilized tumor bone for reconstruction provide outcome benefits in intercalary osteosarcoma based on the potential immunogenic effect of reimplanted sterilized tumor tissue? Of 720 cases of surgically treated high-grade osteosarcoma patients treated at our institute from 2006 to 2013, 61 had predominantly diaphyseal disease. All patients were nonmetastatic at presentation. Patient and tumor characteristics, treatment details, and local recurrence-free, metastasis-free, and overall survival were compared for 24 patients who had reconstruction with sterilized tumor bone reimplantation vs 37 who did not. Both the groups were well matched in terms of baseline characteristics. Means were compared with the t -test, proportions with the chi-square test, and survival with the log-rank test. The Kaplan‐Meier method was used to construct time to event curves. Cox proportional hazard regression modeling was employed for multivariate time to event analysis. Twenty-two had extracorporeal radiation and reimplantation (ECRT) with or without the vascularised fibula. Fifty-gray single dose was used in all cases. Two had pasteurization and reimplantation. Thirty seven had non-reimplantation reconstructions (including intercalary or osteoarticular endoprosthesis, pedicled bone grafts, rotation-plasty, and amputations). Five-year local recurrence-free survival was 85% for reimplantation and 97% for non-reimplantation groups (p = 0.17 ). Five-year metastasis-free survival was 63% and 54%, respectively (p = 0.44 ). Five-year overall survival was 70% and 58%, respectively (p = 0.39 ). The data from this study did not demonstrate significantly better local recurrence-free, distant relapse-free, or overall survival benefit in the tumor bone reimplantation group.